posted by JaneLee on .
Solve: (2x – 3)(3x – 5) = 0
Solve by the quadratic formula. Leave the square root in your answer:
3x2 – x – 8 = 0
Factor the first one by setting each term equal to 0.
2x - 3 = 0
2x = 3
x = 3/2
Do the same process for 3x - 5.
For the second, look over the Quadratic Formula. It states that for an equation ax^2 + bx + c, x will equal the opposite of b plus or minus the square root of b squared minus 4ac all over 2a. (Look it up for the formula equation. It's difficult to type.) All you have to do is identify a, b, and c, and then plug it into the QF. You will have two answers, one using the plus and one using the minus.